Welcome to Sparklegrove - Elliott, Rebecca (2023)
Bo Tinseltail and friends welcome a jackalope family to Sparklegrove Forest, and when they learn the family is being chased by centaurs everyone bands together to help the jackalopes live in peace.
Ages 5-7.
Grades K-1.
Keywords: Unicorns -- Fiction; Mythical animals -- Fiction; Bullies and bullying -- Fiction; Helpfulness -- Fiction; Diaries -- Fiction; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Animals / Dragons, Unicorns & Mythical